Implementasi Program Kalimasada Dalam Meningkatkan Kesadaran Administrasi Penduduk Di Kelurahan Gunung Anyar Kota Surabaya - Shahira, Sharifah; Tukiman, Tukiman (Peneliti.net, 2024)
KALIMASADA program (Environmental Area Community Aware Civil Administration) is an innovation of the Surabaya City Government to create up-to-date civil data by realizing fast and efficient services with document processing simply through RT or RW Hall services. With the ease of processing these documents, it is hoped that the level of administrative awareness among the citizens of Surabaya City will increase. This research aims to analyze the implementation of the KALIMASADA Program in increasing administrative awareness of the civil in Gunung Anyar Village based on the implementation variables identified by Edward III, namely communication, resources, disposition, and bureaucratic structure. This research uses a descriptive-qualitative method with data collection techniques through direct field observation, interviews, and documentation. The results of this research show that the implementation of the KALIMASADA Program in Gunung Anyar Village has gone well even though several obstacles were found, namely in the communication and resource variables because RTs were still found to be less enthusiastic about implementing this program and less than optimal human resources or staff in implementing KALIMASADA because the majority of RW assistants are not special service officers.